2020
DOI: 10.3390/app10186485
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Rapid Maxillary Expansion with or without Previous Adenotonsillectomy for Pediatric Obstructive Sleep Apnea Syndrome Based on Polysomnographic Data: A Systematic Review and Meta-Analysis

Abstract: Aim: To systematically review international literature related to rapid maxillary expansion (RME) as the treatment for obstructive sleep apnea syndrome (OSAS) in children less than 18 years-old, followed by a meta-analysis of the apnea-hypopnea index (AHI) before and after RME, with or without a previous adenotonsillectomy (AT). Methods: Literature on databases from PubMed, Wiley online library, Cochrane Clinical Trials Register, Springer link, and Science Direct were analyzed up to March 2020. Two independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 46 publications
0
16
0
4
Order By: Relevance
“…This aspect is directly linked with what is mentioned in the introduction section, since it is observed that overweight is one of the predisposing factors of OSAS, and it is a common aspect in catering workers. Diagnosis and treatment of OSAS is very relevant for the health of the population [ 13 , 15 ]. Dentists should detect signs and symptoms of obstructive sleep apnea syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This aspect is directly linked with what is mentioned in the introduction section, since it is observed that overweight is one of the predisposing factors of OSAS, and it is a common aspect in catering workers. Diagnosis and treatment of OSAS is very relevant for the health of the population [ 13 , 15 ]. Dentists should detect signs and symptoms of obstructive sleep apnea syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were illustrated by Marty et al 2017 [ 36 ] stating that custom-fitted MAD improved respiratory and somnolence parameters, with response rates similar to those published in the literature with other devices. Moreover, Quinzi et al conducted a meta-analysis on 102 children affected by obstructive sleep apnea syndrome and concluded that on a mean follow-up duration of ≤3 years, a decrease of 66.1% of apnea-hypopnea index was detected in the sample after rapid maxillary expansion treatment [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a 4-5-month window during which the bone physiology changes, where the trabecular bone loses density and selectively offers less resistance to OTM. In AOO (Accelerated Osteogenic Orthodontics), non-activated teeth provide a relative anchorage for activated teeth that move faster (Figure 3) [33,65,66]. Several studies have been conducted to investigate the efficacy of this strategy.…”
Section: Corticotomiesmentioning
confidence: 99%